2015
DOI: 10.1039/c5ta01182e
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric elastomer actuator with excellent electromechanical performance using slide-ring materials/barium titanate composites

Abstract: A dielectric elastomer actuator with excellent electromechanical performance was fabricated by incorporating modified barium titanate into slide-ring materials with necklace-like molecular structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 61 publications
(85 reference statements)
0
51
0
Order By: Relevance
“…The results also indicated that the uniform dispersion of TiO 2 -KH570 particles enhanced interfacial interaction between TiO 2 and SR matrix. Dan Yang et al 26 prepared a slide-ring material with a necklace-like molecular structure as dielectric elastomer materials. BT particles modied by KH570 were added into the SR materials to further increase the actuated performance.…”
Section: Introductionmentioning
confidence: 99%
“…The results also indicated that the uniform dispersion of TiO 2 -KH570 particles enhanced interfacial interaction between TiO 2 and SR matrix. Dan Yang et al 26 prepared a slide-ring material with a necklace-like molecular structure as dielectric elastomer materials. BT particles modied by KH570 were added into the SR materials to further increase the actuated performance.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of high‐permittivity ceramic particles such as BaTiO 3, PZT, ZrO 2 with relative permittivity's in excess of ε r = 1000 or electrically conducting nanoparticles such as graphene and carbon nanotubes, with dielectric elastomers has been considered to generate extrinsically enhanced polymer composites with increased dielectric properties . However, the large difference in relative permittivity and surface energy between the particles and polymer matrices only results in moderate enhancement of the dielectric properties of the composites, and is accompanied by a reduction in breakdown strength and mechanical flexibility, as well as large dielectric loss due to interfacial defects …”
Section: Extrinsic Approaches To Improve the Dielectric Properties Ofmentioning
confidence: 99%
“…Polymer‐based nanocomposites with high dielectric constants (high‐k) have attracted extensive attention for their applications in embedded capacitors, actuators, energy storage devices, and so forth . These materials combine the advantages of fillers, such as high dielectric constant and good electrical conductivity, as well as the merits of polymers, such as proper processing, flexibility, mechanical properties, and high breakdown strength.…”
Section: Introductionmentioning
confidence: 99%